A decade of humpback whale abundance estimates at Bermuda, an oceanic migratory stopover site - Grove, Thomas; King, Ruth; Stevenson, Andrew; Henry, Lea-Anne (Frontiers in Marine Science, 2023)
We constructed annual abundance of a migratory baleen whale at an oceanic stopover site to elucidate temporal changes in Bermuda, an area with increasing anthropogenic activity. The annual abundance of North Atlantic humpback whales visiting Bermuda between 2011 and 2020 was estimated using photo-identification capture-recapture data for 1,204 whales, collected between December 2009 and May 2020. Owing to a sparse data set, we combined a Cormack-Jolly-Seber (CJS) model, fit through maximum likelihood estimation, with a Horvitz-Thompson estimator to calculate abundance and used stratified bootstrap resampling to derive 95% confidence intervals (CI). We accounted for temporal heterogeneity in detection and sighting rates via a catch-effort model and, guided by goodness-of-fit testing, considered models that accounted for transience. A model incorporating modified sighting effort and time-varying transience was selected using (corrected) Akaike’s Information Criterion (AICc). The survival probability of non-transient animals was 0.97 (95% CI 0.91-0.98), which is comparable with other studies. The rate of transience increased gradually from 2011 to 2018, before a large drop in 2019. Abundance varied from 786 individuals (95% CI 593-964) in 2016 to 1,434 (95% CI 924-1,908) in 2020, with a non-significant linear increase across the period and interannual fluctuations. These abundance estimates confirm the importance of Bermuda for migrating North Atlantic humpback whales and should encourage a review of cetacean conservation measures in Bermudian waters, including area-based management tools. Moreover, in line with the time series presented here, regional abundance estimates should be updated across the North Atlantic to facilitate population monitoring over the entire migratory range.